Radar guided mobile robot - Lim, Hui Wen. (2013)
The main objective of this project is to integrate a mobile robot with a radar sensor. By using the radar signal, the mobile robot would be able to navigate autonomously even in an environment with low visibility or many obstacles. The advantages of using a radar sensor versus an optical sensor (camera) is that RF waves have better penetrating capability to enable the system to operate in low-light, foggy, dusty, obstructed environment with debris and rubble. The project will focus on the integration of three major components: a) a mobile robot with motors and wheel control; b) a radar sensor based on the USRP wireless card; c) an on-board computer to process the radar image and control the movement of the robot.